Formative Evaluation Instruments of Integrated Character Education in Thematic Learning - Mertasari, Ni Made Sri; Yudana, I Made (LPPM Undiksha, 2022)
The social, emotional, and ethical domains receive less emphasis on all subjects, except for subjects aimed at moral development, causing many problems. However, due to various limitations, it is not uncommon for education in schools to emphasize the academic realm, which is a provision for students to find provisions for life in the future. This research aims to develop an Integrated Character Education Formative Evaluation Instrument in Thematic Learning. This type of research is development. The integrated character education assessment instrument was developed following the Gregory test development procedure. The methods used in collecting data are questionnaires and observations. The data collection instrument used a questionnaire. The technique used in analyzing the data is descriptive qualitative, and quantitative analysis. The study's results, namely the expert assessment, found that the instrument's content validity was qualitatively feasible and quantitatively. It was also feasible because the Content Validity Ratio (CVR) ranges from 0.80-0.82. The rater's reliability coefficient is 0.78 and has exceeded the eligibility threshold. It was concluded that the instrument could be used for simultaneous character and academic evaluation, both for evaluating learning activities in and outside the classroom with a performance approach.